Stochastic models of heredity rhesus factor - Ganikhodjaev, Nasir; Jamal Ibrahim, Daoud; Usmanova, Makhsuma (INSI Publications, 2010)
We consider linear and nonlinear stochastic models of transmission Rhesus factor from parents to their offspring and show that in long run behavior the frequency of Rhesus factor be the same.